2016
DOI: 10.1016/j.clinthera.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glimepiride versus Saxagliptin on β-Cell Function and Hypoglycemia: A Post Hoc Analysis in Older Patients with Type 2 Diabetes Inadequately Controlled with Metformin

Abstract: In patients with lower β-cell function, the addition of a sulfonylurea to a metformin regimen was associated with an increased risk for hypoglycemia compared with that in patients with higher β-cell function; low hypoglycemia event rates with the addition of saxagliptin limited equivalent assessments. These findings in older patients are especially relevant because morbidity associated with hypoglycemia is higher in this age group. ClinicalTrials.gov identifier: NCT01006603 (ClinicalTrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, in a recent cross‐sectional study, the risk of beta cell stress was nearly 3‐fold higher in subjects with high HbA1c compared with those with lower values. Beta cell function is associated with HbA1c levels both in pre‐diabetic states, where it predicts the progression to T2DM, and in overt diabetes, where it is associated with metabolic control more than with insulin sensitivity …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent cross‐sectional study, the risk of beta cell stress was nearly 3‐fold higher in subjects with high HbA1c compared with those with lower values. Beta cell function is associated with HbA1c levels both in pre‐diabetic states, where it predicts the progression to T2DM, and in overt diabetes, where it is associated with metabolic control more than with insulin sensitivity …”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the addition of glimepiride to metformin was associated with an increased risk of hypoglycaemia in patients with lower compared with higher beta-cell function, suggesting that sulphonylureas should be used with caution in patients with poor beta-cell function. 43 In contrast, GLP-1 RAs have been associated with improvements in beta-cell function. 39,[44][45][46][47][48] Evidence suggests that GLP-1 RAs can modulate insulin secretion by directly stimulating beta-cells or indirectly through weight loss and enhanced insulin sensitivity.…”
Section: Mode Of Action and Effects On Durability Of Glycaemic Control And Bodyweightmentioning
confidence: 99%
“…Regarding diabetic pharmacotherapy, metformin is a biguanide approved for management of T2DM, it possess significant anti-inflammatory and anti-oxidant effects that reducing the cardio-metabolic complications [11], additionally, metformin improves endothelial function through regulation of endothelial NO and attenuating the inflammatory-induced vascular endothelial function [12]. Alternatively, glimepiride which is a long acting secretagogus sulfonylurea acts through augmentation of peripheral insulin sensitivity and stimulation of insulin secretion from pancreatic β-cells [13]. Generally, sulfonylurea reduced NO production [14] but it is little known about glimepiride effect on nitrate-nitric-NO pathway.…”
Section: Introductionmentioning
confidence: 99%